The language of Wierzchosławice as presented in My Memoirs by Wincenty Witos - Piechnik, Anna (Papers in Linguistics, 2021)
The article aims to present the language, and thus the culture of Wierzchosławice (late 19th, early 20th c.), as depicted in My Memoirs by Winecenty Witos – one of the greatest politicians of the Second Polish Republic. The researchers who analysed his written and oratorical works emphasize his command of the standard Polish language and infrequent use of the local dialect. Nevertheless, analysis of the text shows that the regional dialect of Wierzchosławice is represented in his memoirs. The most common examples of the dialect are lexical items, which are shown graphically or syntactically; less common are phonetic or inflexional features of the local dialect. Witos makes use of words and phrasemes associated with soil cultivation and farming that are foreign to the standard Polish language. He mentions individual and collective nicknames, as well as microtoponyms and individual appellative expressions. In many instances, Witos explicates the semantics and motives supporting the name-forming processes of particular terms, and as a result, the vocabulary is presented as a medium and constituent of axiological and cultural content. In My Memoirs, the local dialect functions as a linguistic identifying mark of the region.